Caveolae-Specific CaMKII Signaling in the Regulation of Voltage-Dependent Calcium Channel and Cardiac Hypertrophy - Tanaka, Shota; Fujio, Yasushi; Nakayama, Hiroyuki (Frontiers in Physiology, 2018)
Cardiac hypertrophy is a major risk for the progression of heart failure; however, the underlying molecular mechanisms contributing to this process remain elusive. The caveolae microdomain plays pivotal roles in various cellular processes such as lipid homeostasis, signal transduction, and endocytosis, and also serves as a signaling platform. Although the caveolae microdomain has been postulated to have a major contribution to the development of cardiac pathologies, including cardiac hypertrophy, recent evidence has placed this role into question. Lack of direct evidence and appropriate methods for determining activation of caveolae-specific signaling has thus far limited the ability to obtain a definite answer to the question. In this review, we focus on the potential physiological and pathological roles of the multifunctional kinase Ca2+/calmodulin-dependent kinase II and voltage-dependent L-type calcium channel in the caveolae, toward gaining a better understanding of the contribution of caveolae-based signaling in cardiac hypertrophy.